Transforming Natural Values ​​into Architecture: An Intangible Metaphor Approach to Zoological Museum Design - arafatul liza; Qurratul Aini (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2026)
Indonesia, particularly the province of Aceh, boasts an exceptionally high diversity of fauna. This region serves as a habitat for various endemic species, some of which are extinct or endangered. Ideally, this should be brought to the public’s attention by introducing or even studying this rich fauna. However, this effort has not yet been supported by adequate infrastructure. The limited facilities for wildlife education and research raise the research question: “How can we create a space that facilitates education, research, and recreation simultaneously?” In response to this issue, this study presents a design concept for a zoological museum that incorporates the transformation of natural values into architecture. The museum aims to raise public awareness and foster a sense of responsibility regarding the urgency of wildlife and ecosystem conservation. The research method employs an architectural design-based approach using the Intangible Metaphor framework, in which abstract values from nature—such as the philosophy of balance, harmony, the life cycle, and the principle of sustainability—are translated into physical architectural elements. The design results demonstrate that these themes are realized through a building mass composition arranged in a gradual progression from low to high scales, serving as a visual representation of the fauna’s life cycle. In addition, natural materials are used to strengthen the interaction and emotional connection between humans and nature, and the spatial design is both dynamic and exploratory, aiming to create a profound educational experience for visitors. Through this approach, the museum is expected to serve as a leading center for zoological education while also symbolizing the harmonious and sustainable relationship between humans and nature.